2013
DOI: 10.3389/fimmu.2013.00206
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biophysical Insights into the Role of CD4 and CD8 in T Cell Activation

Abstract: T cell receptors (TCRs) recognize peptides presented by MHC molecules (pMHC) on an antigen-presenting cell (APC) to discriminate foreign from self-antigens and initiate adaptive immune responses. In addition, T cell activation generally requires binding of this same pMHC to a CD4 or CD8 co-receptor, resulting in assembly of a TCR–pMHC–CD4 or TCR–pMHC–CD8 complex and recruitment of Lck via its association with the co-receptor. Here we review structural and biophysical studies of CD4 and CD8 interactions with MH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 84 publications
(156 reference statements)
0
54
0
Order By: Relevance
“…MHC, also called H-2 antigens (histocompatibility-2 antigens) in mice and HLA antigens (human-leucocyte-associated antigens) in humans, can be separated into two classes. Class I MHC (MHC-I) are expressed by all cells in our body and bind to TCRs associated with the co-receptor CD8, on CD8 + T cells, while Class II MHC (MHC-II) are only expressed on antigen presenting cells (APC), such as dendritic cells (DC) or macrophages, and bind to TCRs associated with CD4, on CD4 + T cells [194]. After activation, and based on the cytokines they will be exposed to, naïve CD4 + T cells (Th0) can polarize into other subsets such as the classical T-helper 1 (Th1), 2 (Th2), or 17 (Th17), or induced T-regulatory cells (iTreg) [195].…”
Section: T Cellsmentioning
confidence: 99%
“…MHC, also called H-2 antigens (histocompatibility-2 antigens) in mice and HLA antigens (human-leucocyte-associated antigens) in humans, can be separated into two classes. Class I MHC (MHC-I) are expressed by all cells in our body and bind to TCRs associated with the co-receptor CD8, on CD8 + T cells, while Class II MHC (MHC-II) are only expressed on antigen presenting cells (APC), such as dendritic cells (DC) or macrophages, and bind to TCRs associated with CD4, on CD4 + T cells [194]. After activation, and based on the cytokines they will be exposed to, naïve CD4 + T cells (Th0) can polarize into other subsets such as the classical T-helper 1 (Th1), 2 (Th2), or 17 (Th17), or induced T-regulatory cells (iTreg) [195].…”
Section: T Cellsmentioning
confidence: 99%
“…CD4 + T cells (also known as “helper cells”) express the CD4 protein on the cell surface. Upon ligation of the TCR to a cognate MHC II, the CD4 protein will also bind to the MHC II molecule [36] (Fig. 3f).…”
Section: T Cell Mediated Immune Responsesmentioning
confidence: 99%
“…Among the findings, it has been shown that the variable (V) domains of each chain bind to the specific peptide/MHC ligand in a conserved, diagonal orientation. The structural basis of this invariant orientation is still unclear, but it has been suggested to be due to the: 1) geometry required for the entire T cell complex (αβ TCR, CD3 subunits, and co-receptor CD4 or CD8) to productively engage the pepMHC and to signal the T cell during thymic selection [31, 54], 2) evolutionary pressures that yielded “germline” TCR regions with basal affinity for the helices of MHC molecules [22, 34], or 3) perhaps both [29]. …”
Section: Introductionmentioning
confidence: 99%